أهمية استخدام الوسائل التعليمية في تعليم اللغة العربية للناطقين بغيرها - Umar Al-Faruqi (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2014)
Language is a medium of communication for people in society to reveal the intention of his true identity , interests and talents , as well as a medium to improve the knowledge , intellect , and emotions . But is not the case for foreign language learners including learning the Arabic language , which would certainly experience many difficulties and problems.Learning Arabic for foreign speakers had been developed in many parts of the world , but the desired level of success in language learning is still not satisfactory and arguably still very minimal . The success rate of teachers in teaching the Arabic language is still low and not much that can be felt by learners . There are so many constraints and problems faced both by students and by teachers themselves .The using of instructional media in teaching of the Arabic language for foreign speakers is regarded as a successful solution to solve the existing problems , because it is the creativity of teachers in selecting and using instructional media in accordance with the elements and language skills play an important role in the success of teaching and learning Arabic Process for foreign speakers in the classroom .Therefore , I will describe the importance of the use of instructional media in teaching Arabic for foreign speakers where its presence in learning Arabic is deemed to be able to make the learning process more active , innovative , not boring, and fun.